Dal saggio dell’edificio B. Novità per lo studio della ceramica etrusca figurata a Tarquinia (Aristonothos. Rivista di Studi sul Mediterraneo Antico, 2019)
This paper presents an important group of figurative ceramic (black-figure, red-figure, superposed colour) discovered during P. Romanelli’s excavations of the Civita of Tarquinia. Together with the materials recently discovered during the excavations by the Università degli Studi di Milano at the ‘monumental complex’ and at the Ara della Regina, these fragments show the dissemination of figured pottery in Tarquinian non-funerary contexts. Their analysis adds important data on the diffusion of groups such as the Uccelli acquatici Group or the Funnel Group. In this regard, an unusually decorated fragment belonging to the Tarquinian Silhouette Workshop, recognised as a Tarquinian production by M. Del Chiaro, is particularly interesting. For this reason, the second part of this work is dedicated to this fragment.
Keywords: Etruscan Figured pottery; Tarquinia Civita; P. Romanelli; Superposed colour pottery; Tarquinian Silhouette workshop; Funnel Group; Sokra group